2002
DOI: 10.1007/s005350200016
|View full text |Cite
|
Sign up to set email alerts
|

Irritant-induced cyclooxygenase-2 is involved in the defense mechanism of the gastric mucosa in mice

Abstract: Pretreatment-induced COX-2, in addition to COX-1, seemed to be involved in the defense mechanism through minimizing the damage caused by a subsequent irritant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…First, we examined the localization of COX-2-expressing cells in the stomach of ethanol-treated mice to determine the cells expressing COX-2 in vivo. We expected to detect COX-2 protein in ethanol-treated gastric mucosa as shown by Miyake et al (28) and Bhandari et al (2). We were, however, unable to obtain a clear COX-2 signal in the mucosa of our gastric tissue specimens (data not shown).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…First, we examined the localization of COX-2-expressing cells in the stomach of ethanol-treated mice to determine the cells expressing COX-2 in vivo. We expected to detect COX-2 protein in ethanol-treated gastric mucosa as shown by Miyake et al (28) and Bhandari et al (2). We were, however, unable to obtain a clear COX-2 signal in the mucosa of our gastric tissue specimens (data not shown).…”
Section: Discussionsupporting
confidence: 53%
“…The stomachs were removed without using the perfusion process, sectioned horizontally, and either fixed in 10% buffered formalin for histochemistry or immediately frozen in liquid nitrogen for the analysis of RNA, protein, and PGE2. The histologic extent of the gastric mucosal injury was evaluated by a pathologist as the percentage of the length of microscopically identified mucosal injury, which comprised hemorrhage and disruption of gastric epithelial cells to the length of the circumference of the gastric corpus, according to the method described by Miyake et al (28).…”
Section: Methodsmentioning
confidence: 99%
“…We should be cautious, therefore, in extrapolating these findings to other mouse strains and should consider taking a multistrain approach in mouse prostanoid research. Furthermore, some of the reports on the role of prostaglandins in gastric acid secretion have been published without mention of the mouse strain used (22,23). Our RT-PCR revealed that the strain difference we have characterized pharmacologically is related to lower expression of message for the EP 3 receptor in gastric mucosa from C57BL/6 than from BALB/c mice.…”
Section: Discussionmentioning
confidence: 73%
“…Although such low taurocholate doses did not provoke severe gastric damage, this taurocholateinduced adaptive cytoprotection lasted for over 5 h; the early phase shown to be mediated mainly by COX-1, and the latter phase by both COX-1 and COX-2 (29). We also found that, COX-2, induced 24 h after pretreatment with a mild irritant, serves as a defense mechanism by minimizing subsequent irritant-induced damage (30). Taking all these studies into consideration, it is now clear that COX-2 expressed in the injured mucosa plays a significant role in the repair process and in the defense mechanism of the stomach.…”
Section: Role Of Cox-2 In the Gastric Mucosamentioning
confidence: 73%